Evaluation of groundnut germplasm for pod yield and its attributes in summer: Evaluation of groundnut germplasm for pod yield and its attributes in summer - K GANGADHARA; A L RATHNAKUMAR; PRAVEEN KONA; B C AJAY; NARENDRA KUMAR; SUSHMITA; H K GOR (Journal of Oilseeds Research, 2020)
Forty eight germplasm collections were evaluated for pod yield and its attributes during summer 2018 and 2019. High heritability coupled with high GAM were observed for pod yield per plant, HPW, HKW and kernel length indicating that selection for these characters could be more effective due to additive gene action. Pod yield per plant correlated significantly and positively with SP, SMK, and kernel length to width ratio. Both DFI and DFF correlated significantly and negatively with pod yield per plant. SLA had low heritability and GAM. Genotypes NRCG 14507, NRCG CS 254, NRCG CS 313 and Girnar 1 showed early flowering initiation (35 DAS). The surrogate trait of water use efficiency (SLA) was lowest (150<) in genotypes viz., NRCG 17284, SG 99, Gangapuri, ICGS 9114 and VRI 3. Genotypes viz., JGN3, NRCG CS 62, TMV9, ICGS 76, NRCG 8763 showed higher shelling percentage (>70%). Genotypes NRCG 10620 and TG 39 exhibited higher yields over two summer seasons.